2009
DOI: 10.1097/ajp.0b013e3181805a1e
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-cultural Study of the Back Pain Beliefs of Female Undergraduate Healthcare Students

Abstract: Findings of this study highlight the importance of country, education, and LBP experience on back pain beliefs. The more negative back pain beliefs found in Taiwan and Singapore may reflect current pain beliefs and management attitudes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
61
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 52 publications
14
61
4
Order By: Relevance
“…Maybe this can explain the low test-retest reliability. The internal consistency was shown to be good (0.83), similar to the 0.78 value in the original version [13] and to the 0.83 in the Dutch version [14] but higher than the 0.72 reported for the Chinese version [15]. Rainville in the English and Houben in the Dutch versions suggested that items 10 and 13 should be deleted as their deletion raised the value of Cronbach's alpha and these two items correlated much less with the other factors.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…Maybe this can explain the low test-retest reliability. The internal consistency was shown to be good (0.83), similar to the 0.78 value in the original version [13] and to the 0.83 in the Dutch version [14] but higher than the 0.72 reported for the Chinese version [15]. Rainville in the English and Houben in the Dutch versions suggested that items 10 and 13 should be deleted as their deletion raised the value of Cronbach's alpha and these two items correlated much less with the other factors.…”
Section: Discussionmentioning
confidence: 53%
“…In our study the average responses also were trended towards agreement (item 10: 4.77 and item 13: 4.36) but revealed good correlation with the tendency given in the other items. Some studies have found differences in how back pain is faced among different cultural backgrounds by patients [30] and by health care providers [15,16]. For example, Kovacs et al [18] demonstrated that in Spanish LBP patients the influence of fearavoidance beliefs is sparse in disability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study showed that Australian physical therapy students had a total score of 40.2 on HC-PAIRS. 13 Although it was not significant, Burnett et al 17 found a higher HC-PAIRS total score in Singaporean (61.5) and Taiwanese (60.8) compared with Australian (57.8) physical therapy students. Briggs et al 13 found that physical therapy students reported more helpful beliefs than students from other disciplines, namely, chiropractic, medicine, occupational therapy, and pharmacy.…”
Section: Discussionmentioning
confidence: 95%